How to survive in the world’s third poplar: Insights from the genome of the highest altitude woody plant, Hippophae tibetana (Elaeagnaceae) - Wang, Ruoqiu; Wu, Bin; Jian, Jianbo; Tang, Yiwei; Zhang, Ticao; Song, Zhiping; Zhang, Wenju; Qiong, La (Frontiers in Plant Science, 2022)
Hippophae tibetana (Tibetan sea-buckthorn) is one of the highest distributed woody plants in the world (3,000-5,200 m a.s.l.). It is characterized by adaptation to extreme environment and important economic values. Here, we combined Pacbio Hifi platform and Hi-C technology to assemble a 1,452.75 Mb genome encoding 33,367 genes with a contig N50 of 74.31 Mb, and inferred its sexual chromosome. Two Hippophae-specific whole-genome duplication events (18.7-21.2 Ma; 28.6-32.4 Ma) and long terminal repeats retroelements (LTR-RTs) amplifications were detected. Comparing with related species at lower altitude, Ziziphus jujuba (<1700 m a.s.l.), H. tibetana had some significantly rapid evolving genes involved in adaptation to high altitude habitats, but pollen recognition-related genes evolved significantly slow in H. tibetana. However, comparing with Hippophae rhamnoides (<3700 m a.s.l.), no rapid evolving genes were found except microtubule and microtubule-based process genes, H. tibetana has a larger genome, with extra 2503 genes (7.5%) and extra 680.46 Mb transposable elements (TEs) (46.84%). These results suggest that the changes in the copy number, expression level and regulatory pattern of genes play a more important role for H. tibetana adapting to more extreme and variable environments at higher altitude by more TEs and more genes increasing genome variability and expression plasticity. This suggestion was supported by two findings: nitrogen-fixing genes of H. tibetana having more copies, and intact TEs being significantly closer genes than fragmentary TEs. This study provided new insights into the evolution of alpine plants.